University Students and Their Ability to Perform Self-Regulated Online Learning Under the COVID-19 Pandemic - Klimova, Blanka; Zamborova, Katarina; Cierniak-Emerych, Anna; Dziuba, Szymon (Frontiers in Psychology, 2022)
The Covid-19 pandemic has affected all aspects of the educational system, including students’ learning styles, which are heavily dependent on self-regulated studying strategies and motivation. The purpose of this study was to discover whether Central European students, in this case the Slovak and Czech students, were able to perform self-regulated learning during online learning under the Covid-19 pandemic to achieve their learning goals and improve academic performance. The methodology was based on a questionnaire survey conducted among 268 students at two Central European universities in February and March 2021. The findings indicate that Central European students seemed to be well-prepared for online self-study, especially in regard to personal competencies, meaningfulness and motivation. They were particularly aware of their strengths and weaknesses in learning, time management, and/or the usefulness of making an effort to study. However, the findings show that much more work must be done in the area of metacognitive strategies, such as reflective and critical thinking, analyzing and evaluating. In this respect, it is the teacher who can serve as a facilitator and promote these metacognitive strategies by providing students with constructive feedback, monitoring their learning, reviewing their progress, and/or providing opportunities to reflect on their learning.